2012
DOI: 10.1177/2047487312460022
|View full text |Cite
|
Sign up to set email alerts
|

T-wave inversion on electrocardiogram is related to the risk of acute coronary syndrome in the general population

Abstract: TWI has a strong and independent predictive value for ACS in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Several reports from different populations have shown that ECG abnormalities reflect increased risk of CVD . Thus, our finding of higher occurrence of new ECG abnormalities in patients with T1D highlights the increased risk of CVD in this population as they age.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Several reports from different populations have shown that ECG abnormalities reflect increased risk of CVD . Thus, our finding of higher occurrence of new ECG abnormalities in patients with T1D highlights the increased risk of CVD in this population as they age.…”
Section: Discussionsupporting
confidence: 68%
“…Several reports from different populations have shown that ECG abnormalities reflect increased risk of CVD. [2][3][4][5][6][7][8][9][10][11][12][13] Thus, our finding of higher occurrence of new ECG abnormalities in patients with T1D highlights the increased risk of CVD in this population as they age. Notably, the reported prevalence of ECG abnormalities in the general population using the same ECG classification system range from 16% to 32%, [22][23][24][25][26] which is lower than rates observed in our study population of T1D.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations